2014
DOI: 10.1108/f-03-2012-0024
|View full text |Cite
|
Sign up to set email alerts
|

An urban growth model of office property development

Abstract: 2014),"Supply network design in the residential-FM sector: A service provider perspective", Facilities, Vol. 32 Iss 11/12 pp. 723-738 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…Given that the predictive power of the model in this study is low (0.109), it is not surprising because of the nature and the context of the study area. There are other factors responsible for shrinking office space in Hong Kong such as limited land space, high density, and high rent (Wadu Mesthrige, 2014). For instance, office spaces are likely to shrink as rents soar.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Given that the predictive power of the model in this study is low (0.109), it is not surprising because of the nature and the context of the study area. There are other factors responsible for shrinking office space in Hong Kong such as limited land space, high density, and high rent (Wadu Mesthrige, 2014). For instance, office spaces are likely to shrink as rents soar.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In the model estimations, various lags were considered for the variables utilised in systems of demand and supply equations. Some other recent examples on the existence of lagged variables utilised in explaining the adjustment processes in demand and supply relationship in commercial and industrial property markets can be found in Fuerst and Grandy [ 54 ], White and Ke [ 55 ], Mesthrige [ 56 ], Bruneau and Cherfauh [ 57 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, AFM has been utilized to image a variety of biological specimens including cells, proteins, and DNA at nanometre resolution. [13][14][15][16][17][18][19][20] AFM enables protein molecules to be visualized in buffer with nanometre resolution in threedimensions. [21][22][23][24][25][26] In fact, our prior work has demonstrated that AFM enabled high-resolution imaging of BMP-2/COMP complexes.…”
Section: Introductionmentioning
confidence: 99%